Local-Cosmopolitan Orientations and Career Strategies for Specialists - Delbecq, André L.; Elfner, Eliot S. (Academy of Management Journal, 1970)
The research reported sought to operationalize the Thompson, Avery, and Carlson model for career strategies, and to relate these strategies to occupational orientation toward either the employing organization (local) or the speciality (cosmopolitan). The resulting modified conceptualization was tested using a sample of veterinarian scientists employed by a government agency. Results indicated that the operationalization of the modified Thompson model was successful. Further, scientists choosing a stable career strategy seemed to have a low occupational orientation relative to their speciality. However, scientists choosing an organizational strategy seemed to be both oriented toward their speciality and their organization.